2015
DOI: 10.1002/ejlt.201400420
|View full text |Cite
|
Sign up to set email alerts
|

Fat crystallization with talc particles is influenced by particle size, concentration, and cooling rate

Abstract: We recently found that new types of additives including talc promoted the crystallization of monoacid saturated triacylglycerols (TAGs) in stable polymorphs. This study reports the effects of size and concentration of talc particles and cooling rate on the crystallization of trilauroylglycerol (LLL), tripalmitoylglycerol (PPP), and 1,3-dipalmitoyl-2-oleoyl glycerol (POP). Talc particles were mixed with molten TAGs, and the mixtures were then cooled at designated cooling rates. Polymorphic crystallization was o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…However, a high concentration of these additives is needed for the template effects due to their solubility in fats . Our recent study revealed that fat crystallization was promoted especially by adding foreign crystals of talc, carbon nanotube, graphite, theobromine, ellagic acid dihydrate, or terephthalic acid, despite their molecular dissimilarity to fats . Such promotional effects are expected even at low concentrations of these materials because their crystals are thermally stable and sparingly soluble in fats.…”
Section: Introductionmentioning
confidence: 99%
“…However, a high concentration of these additives is needed for the template effects due to their solubility in fats . Our recent study revealed that fat crystallization was promoted especially by adding foreign crystals of talc, carbon nanotube, graphite, theobromine, ellagic acid dihydrate, or terephthalic acid, despite their molecular dissimilarity to fats . Such promotional effects are expected even at low concentrations of these materials because their crystals are thermally stable and sparingly soluble in fats.…”
Section: Introductionmentioning
confidence: 99%
“…Yoshikawa et al. [ 80 ] suggested that talc possibly acts as heterogeneous nucleation surface via nucleophilic attack of the hydroxyl group of talc on the carbonyl group of TAG molecules. This attracts TAG molecules on the surface of talc particles and allows the TAG molecules to interact and form a nucleus.…”
Section: Seeding Agentsmentioning
confidence: 99%
“…[ 56 ] Further study by the same group of researchers found that covering the hydrophilic surface of talc does not affect its ability to enhance crystallization. [ 80 ] This indicates that the hydrophilic site of talc possibly does not interfere with the ability of the seeding agents to act as a fat modifier but only the hydrophobic site of the talc molecules that had contributed to its fat modifying property. Like sugar, the effectiveness of talc as seeding agents is dose‐dependent and increases with a decrease in size as more surfaces were exposed.…”
Section: Seeding Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The alkyl chains of these compounds are considered to act as templates for the heterogeneous nucleation by interacting with the hydrocarbon-chain moieties of fat molecules and supporting their ordering processes [ 2 , 3 ]. In contrast, recent studies found that some inorganic and organic crystals (i.e., talc, carbon nanotube, graphite, theobromine, ellagic acid dihydrate, and terephthalic acid) promoted fat crystallization in thermodynamically stable polymorphs [ 4 , 5 ]. These additives are sparingly soluble in lipids and possess no long hydrocarbon chains in their chemical structure, which implies that the additive surfaces attract fat molecules strongly and urge them to form crystal nuclei.…”
Section: Introductionmentioning
confidence: 99%